2016
DOI: 10.1038/srep20596
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitisation of human colorectal cancer cells by ruthenium(II) arene anticancer complexes

Abstract: Some of the largest improvements in clinical outcomes for patients with solid cancers observed over the past 3 decades have been from concurrent treatment with chemotherapy and radiotherapy (RT). The lethal effects of RT on cancer cells arise primarily from damage to DNA. Ruthenium (Ru) is a transition metal of the platinum group, with potentially less toxicity than platinum drugs. We postulated that ruthenium-arene complexes are radiosensitisers when used in combination with RT. We screened 14 ruthenium-arene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…3d, the SER of the designed prodrug Ir-NB was much higher than that of cisplatin (SER: 4.36) and other metalbased RSs reported in the literature. [30][31][32][33][34] These results indicated that the cancer-targeting delivery system facilitates the sensitization efficiency of the RS in curing malignant cells. The synergistic effect was further conrmed by the clonogenic survival assay ( Fig.…”
Section: In Vitro Radiosensitization Effect Of the Ir-based Rssmentioning
confidence: 81%
“…3d, the SER of the designed prodrug Ir-NB was much higher than that of cisplatin (SER: 4.36) and other metalbased RSs reported in the literature. [30][31][32][33][34] These results indicated that the cancer-targeting delivery system facilitates the sensitization efficiency of the RS in curing malignant cells. The synergistic effect was further conrmed by the clonogenic survival assay ( Fig.…”
Section: In Vitro Radiosensitization Effect Of the Ir-based Rssmentioning
confidence: 81%
“…The concentration required for radiosensitization by Ru1 offers a significant improvement over previous work using the multi-intercalator [Ru(dppz) 2 (PIP) 2+ ] 23 and is similar to more cytotoxic Ru(arene)-halide monocationic complexes, which – like cisplatin – rely upon metal-centred reactivity and the formation of coordination bonds with DNA. 56 …”
Section: Resultsmentioning
confidence: 99%
“…Several ruthenium complexes exhibit potent cytotoxic activity to cancer cells [ 27 29 ]. Moreover, selected ruthenium complexes are under phase I or II clinical trials, with promising results [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%